2022
DOI: 10.1155/2022/8025055
|View full text |Cite
|
Sign up to set email alerts
|

GPX8 as a Novel Prognostic Factor and Potential Therapeutic Target in Primary Glioma

Abstract: One of the most prevalent malignant primary brain tumors is primary glioma. Although glutathione peroxidase 8 (GPX8) is intimately associated with carcinogenesis, its function in primary gliomas has not yet been thoroughly understood. Here, we leveraged Chinese Glioma Genome Atlas (CGGA), The Cancer Genome Atlas (TCGA), and Genotype-Tissue Expression (GTEx) database to investigate the association between GPX8 and overall survival (OS) of patients with primary gliomas, and our results showed that GPX8 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In fact, GPx-8 is similar to GPx-7 in that both have low glutathione peroxidase activity while having a function related to promoting the oxidative folding of endoplasmic reticulum proteins and reducing oxidative stress [ 76 ]. It contains an N-terminal signal peptide and a C-terminal endoplasmic reticulum membrane localization signal and functions in regulating calcium homeostasis [ 77 , 78 ]. Importantly, the overexpression of GPx-8 reduces histamine-induced Ca 2+ storage and release in the endoplasmic reticulum [ 77 ]; thus, GPx-8 overexpression results in decreased Ca 2+ levels in the endoplasmic reticulum while its silencing causes Ca 2+ release from the endoplasmic reticulum to the mitochondria and cytoplasm [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, GPx-8 is similar to GPx-7 in that both have low glutathione peroxidase activity while having a function related to promoting the oxidative folding of endoplasmic reticulum proteins and reducing oxidative stress [ 76 ]. It contains an N-terminal signal peptide and a C-terminal endoplasmic reticulum membrane localization signal and functions in regulating calcium homeostasis [ 77 , 78 ]. Importantly, the overexpression of GPx-8 reduces histamine-induced Ca 2+ storage and release in the endoplasmic reticulum [ 77 ]; thus, GPx-8 overexpression results in decreased Ca 2+ levels in the endoplasmic reticulum while its silencing causes Ca 2+ release from the endoplasmic reticulum to the mitochondria and cytoplasm [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that GPX8 can maintain the invasive mesenchymal-like phenotype of breast cancer cells through the IL-6/STAT3 axis [23]. GPX8 has been recognized as a prognostic marker for cancers such as gastric cancer and primary glioma [24,25]. In clear cell renal cell carcinoma, GPX8 silencing inhibits tumorigenesis by regulating nicotinamide N-methyltransferase (NNMT) [26].…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of accidental falls are critical events that demand attention in the care of patients with long-term CKD, as neglecting them may lead to severe consequences [1][2][3] . Chronic kidney disease (CKD) is a kidney disease due to pathological changes or functional reduction of the kidney that lasts for more than 3 months 4,5 . Without timely treatment, CKD may gradually progress to end-stage kidney disease (ESKD), which is difficult to treat 6 .…”
Section: Introductionmentioning
confidence: 99%